Pay Satisfaction and Role Ambiguity as Predictors of Job Burnout Among Osun State Civil Servants, Nigeria - Ayinde, Adeboye T.; Obawole, Aderemi (European Scientific Journal, ESJ, 2019)
The study assessed the levels of Job burnout and examined the extent to which pay satisfaction predicted job burnout among Osun State civil servants. It also investigated the extent to which role ambiguity predicted job burnout and determined whether there is a joint prediction of pay satisfaction and role ambiguity on job burnout. These were with a view to understanding the factors that predict job burnout among Osun State civil servants. The study adopted the descriptive survey design. Primary data were collected through the administration of questionnaire on a sample of the study population. The study adopted multi-stage sampling technique. Purposive sampling technique was used to select eight ministries and stratified sampling technique was used to select 354 respondents comprising 214 males and 140 females with mean age of 43.39 years and standard deviation of 9.09. Three standardized psychological instruments namely: Pay Satisfaction Questionnaire (PSQ), Role Ambiguity Scale and Maslach Burnout Inventory (MBI) were used to collect the data for the study. The data generated was subjected to linear and multiple regression analyses.Â The results revealed that civil servants exhibited a moderate level of job burnout (44.70%). The results also showed that pay satisfaction significantly predicted job burnout among civil servants (Î²= 0.21, t = 3.53,P< .05). The results further revealed that role ambiguity significantly predicted job burnout among the respondents (Î²= 0.71, t = 8.37,P<.05). Finally, the results indicated that pay satisfaction and role ambiguity jointly predicted job burnout among civil servants (Î²= 28.13, t = 9.39,P< .05). The study concluded that job burnout was moderate among Osun State civil servants, while pay satisfaction and role ambiguity independently and jointly predicted job burnout among respondents.